2005
DOI: 10.1103/physrevd.71.034013
|View full text |Cite
|
Sign up to set email alerts
|

O(αs2)QCD corrections to the electroproduction of hadrons with high transverse momentum

Abstract: We compute the order α 2 s corrections to the one particle inclusive electroproduction cross section of hadrons with non vanishing transverse momentum. We perform the full calculation analytically, and obtain the expression of the factorized (finite) cross section at this order. We compare our results with H1 data on forward production of π 0 , and discuss the phenomenological implications of the rather large higher order contributions obtained in that case. Specifically, we analyze the cross section sensitivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 25 publications
(52 reference statements)
7
75
0
Order By: Relevance
“…Specifically, we have demonstrated that the pQCD framework based on factorized cross sections can consistently account for a large variety of processes with hadrons in the final-state with remarkable precision, producing at the same time accurate and universal sets of fragmentation functions. The availability of these crucial non-perturbative inputs now opens a wide range of possibilities for detailed studies of the nu- cleon structure at NLO accuracy through single-inclusive hadroproduction processes, encompassing the study of the spin and flavor structure with polarized SIDIS measurements [26], in proton-proton collisions [27], and in photoproduction [28], the modification of parton densities by nuclear effects [29], or studies of high p T electroproduction processes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we have demonstrated that the pQCD framework based on factorized cross sections can consistently account for a large variety of processes with hadrons in the final-state with remarkable precision, producing at the same time accurate and universal sets of fragmentation functions. The availability of these crucial non-perturbative inputs now opens a wide range of possibilities for detailed studies of the nu- cleon structure at NLO accuracy through single-inclusive hadroproduction processes, encompassing the study of the spin and flavor structure with polarized SIDIS measurements [26], in proton-proton collisions [27], and in photoproduction [28], the modification of parton densities by nuclear effects [29], or studies of high p T electroproduction processes [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the following (and throughout the paper) we will only consider the so-called metric contribution [44][45][46][47], i.e. we contract w µν with −g µν and write w = [−g µν w µν ] below.…”
Section: A Three-gluon Correlation Functionsmentioning
confidence: 99%
“…They are expected to be adequate (at least qualitatively) for achieving a good theoretical description at large transverse momentum, q T ∼ Q. In the unpolarized case, the complete next-to-leading (NLO) (O(α 2 s )) corrections to the q T -distribution have been calculated [11,12,13] which will lead to an improvement of the theoretical calculation at large q T . 1 At low transverse momentum, q T ≪ Q, fixed-order calculations are bound to fail.…”
Section: Introductionmentioning
confidence: 99%